2010
DOI: 10.1055/s-0029-1245440
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Brain Metastases of Bronchial Carcinomas with 7 T MRI – Initial Results

Abstract: Our preliminary results indicate that despite the higher spatial resolution the detection of brain metastases on 7 T MPRAGE images is almost equal to 1.5 T MPRAGE images. The 7 T SWI sequence with spatially higher resolution allowed the detection of 20 % more microhemorrhages in brain metastases compared to the 1.5 T SWI sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…The current neurocognitive frameworks for understanding changes in QOL over time requires further refinement and would benefit from the development of imaging biomarkers of radiation effects in order to gain additional insights into the pathogenesis of treatment-related brain injury. To date, there have been no definitive studies to identify specific brain regions that are most vulnerable to radiotherapy, although some authors have suggested that the hippocampus may be particularly sensitive to RT (2933), and that visual attention and memory are disproportionately impaired in late radiation damage (28, 3436). …”
Section: Discussionmentioning
confidence: 99%
“…The current neurocognitive frameworks for understanding changes in QOL over time requires further refinement and would benefit from the development of imaging biomarkers of radiation effects in order to gain additional insights into the pathogenesis of treatment-related brain injury. To date, there have been no definitive studies to identify specific brain regions that are most vulnerable to radiotherapy, although some authors have suggested that the hippocampus may be particularly sensitive to RT (2933), and that visual attention and memory are disproportionately impaired in late radiation damage (28, 3436). …”
Section: Discussionmentioning
confidence: 99%
“…Despite the higher spatial resolution of 3T or 7T MRI, Mö nninghoff et al (34) reported that the detection of brain metastases on 7T MP-RAGE images was almost equal to 1.5 T MP-RAGE images. However, they showed 7T susceptibility weighted image (SWI) sequence allowed the detection of 20% more microhemorrhages in brain metastases compared to the 1.5 T SWI sequence.…”
Section: Conventional Mr Findingsmentioning
confidence: 99%
“…With an increasing field strength, the RF field becomes more inhomogeneous and more susceptible to T2* dephasing effects, potentially improving the detection of blood products in brain MRI [12,14] or impeding diagnostics, when imaging abdominal organs with air-tissue interfaces [6].…”
mentioning
confidence: 99%